ANALISIS PEMASARAN BAHAN OLAHAN KARET RAKYAT DI KABUPATEN KUANTAN SINGINGI - Meli Sasmi; Suardi Tarumun; Eliza Eliza (DINAMIKA PERTANIAN, 2013)
The purpose of this research was to recognize the crumb rubber marketing, price transmission, dan market integration in Kuantan Singingi Regency. The research used survey method to collect primary and secondary data. The analysis instruments used were margin and multiple regression analyses with refer to Nerlove Model. The results showed that the best efficient rubber crum channel was found on markeitng channel which was done by farmers joined together into cooperative marketing group by action system. The elasticity value of price at farmer level transmission showed that price was enough response on price changes in trader level in long term as well as short term. The price response at trader level that was resulted by price changes at the fabric level in long term as well as short term was good. Nevertheless, price at the fabric level was not responsive on price changes of FOB in long term as well as short term. Analysis of market integration showed that market at farmer and trader levels was integrated perfectly in which price changes on one market will be followed by other markets with the same proportion. Althought market structure directed to oligopsony form, transaction process showed more clearly on perfect competition market. It is because the good relationship between farmer and trader. The godd integrattion market was also occurred between market at trader level and market at the fabric